Spatiotemporal analysis of regional TIA trends - Kawai, Andrew; Hui, Samuel; Beare, Richard; Srikanth, Velandai K.; Sundararajan, Vijaya; Ma, Henry; Phan, Thanh G. (Frontiers in Neurology, 2022)
Background There has been a decline in the stroke incidence across high income countries including UK but such knowledge exists at Country or State rather than areal unit level such local government area (LGA) level. In this disease mapping study, we evaluate if there are local hot spots or temporal trends in TIA rate. Such knowledge will be of help in planning healthcare service delivery across regions. Methods Linked hospital discharge data (Victorian Admitted Episodes Dataset or VAED) was used to collect TIA (defined by ICD-10-AM codes G450-G459) cases from 2001-2011. The State of Victoria is the second most populous state in Australia, with a population of 6.7 million based on 2016 Census and can be divided into 79 administrative units or LGA. The data is anonymized and contains residence of the patient in terms of LGA but not exact location. The date of the TIA event when the patient is admitted to hospital is provided in the dataset. The number of TIAs per year was aggregated for each LGA. Standardized TIA ratios were calculated by dividing actual over expected cases for each LGA per year. We used Integrated Nested Laplace Approximation (INLA) to perform spatial and spatiotemporal regression, adjusting for hypertension, sex and population, age (≥60), and socio-economic status (SES) decile within the LGA. The final model was chosen based on the lowest the Deviance Information Criterion (DIC) and Watanabe-Akaike information criteria (WAIC). Results Choropleth maps showed a higher standardized TIA ratios in North-West rural region. Compared to the baseline model (DIC 13,159, WAIC 13,261), adding in a spatial random effect significantly improved the model (DIC 6,463, WAIC 6,667). However, adding a temporal component did not lead to a significant improvement (DIC 6,483, WAIC 6,707). Conclusion Our finding suggests a statically significant spatial component to TIA rate over regional areas but no temporal changes. Focussing services in this regional area may lead to improvements in primary prevention of stroke, and stroke care. The finding support investment to explore other countries for similar spatiotemporal patterns.